Meningkatkan hasil belajar pada pembelajaran sifat-sifat cahaya melalui model problem based learning pada siswa kelas IV Sekolah Dasar Negeri 3 Kedungwringin - Tri Mutiah (Jurnal Kualita Pendidikan, 2020)
Classroom action research (CAR) has been carried out to improve learning outcomes through a problem-based learning model. the results of observations of learning the properties of light in grade IV SD Negeri 3 Kedungwringin were not satisfactory. Of the 14 students, only 3 (21.42%) were able to get a grade? 70, while (78.58%) is still below the KKM, namely 70. This Classroom Action Research aims to improve learning outcomes for the properties of light in grade IV SDN 3 Kedungwringin. The CAR procedure is carried out in two cycles through a grooved process consisting of stages, namely planning, action, observation, and reflection. The research subjects were 14-grade students of SDN 3 Kedungwringin. Data analysis is a descriptive statistical analysis. Data collection techniques used direct observation, questionnaires, document review, and student test results. The results of the study in the first cycle, student learning outcomes have increased, namely 8 out of 14 students or (57.14) have been completed with an average value of 67.14. Whereas in cycle II, the completeness of student learning outcomes reached 92.85% or 13 out of 14 students with an average of 92.14. Based on the results of this study, it can be concluded that the use of the problem-based learning model can improve the learning of the properties of light in grade IV SDN 3 Kedungwringin students.